Pemanfaatan Platform Pembelajaran Berbasis Permainan Kahoot! untuk Evaluasi Pembelajaran Bahasa Indonesia Karya Tulis Ilmiah - Jiwandono, Nahnu Robid; Firmansyah, Asep (Universitas Insan Budi Utomo, 2025)
The purpose of this study is to describe the use of Kahoot! Game-based learning platform for learning evaluation in the Indonesian Language and Scientific Writing course. The researcher designed a digital-based learning evaluation instrument using Kahoot! Platform. The instrument consists of 42 multiple-choice questions designed to measure students' understanding of the material presented during the learning process. In general, the scope of the material in this instrument includes the use of Indonesian spelling, effective sentence construction, and technical aspects of writing scientific papers. This study is a qualitative descriptive study. Data were collected through observation and interviews with students who used the Kahoot! Instrument. The data were analyzed using an interactive data analysis model. Based on the research findings, Kahoot! as a learning evaluation instrument in the Indonesian Language and Scientific Writing course was considered more interesting, interactive, and efficient by students who, in this case, fall into the Generation Z category, compared to conventional tests. This platform supports assessment transparency and encourages healthy competition among students taking the test. However, there are still obstacles such as inappropriate time allocation and dependence on a stable internet connection in Kahoot! as a learning evaluation instrument. Overall, Kahoot! It is considered effective but requires technical adjustments for optimal implementation.